RELATIONSHIP OF BODY PERFORMANCE EXERCISES ON SLEEP QUALITY AND ANXIETY ON ACTIVE WOMEN IN JAKARTA - Dinan Mitsalina; Muhammad Imam Rahmatullah; Masnur Ali; Dewi Nurhidayah; Lita Mulia; Anita Puspa Ningrum; Fitri Agung Nanda (MEDIKORA, 2023)
Sleep quality and anxiety are closely related. Those who have difficulty sleeping often have problems with anxiety, and vice versa, those who have difficulty often experience problems sleeping. Sleep quality has a significant effect on anxiety and is influenced by, among others, the type of work, physical activity, physical exercise, and sports. This study aims to determine the relationship between exercise body performance, sleep quality, and anxiety. This research is descriptive research with a survey method. Using purposive sampling with certain criteria. Participants are members of Studio Primadonna. Instruments with online questionnaires: the Pittsburgh Sleep Quality Index (PSQI) for sleep quality and the Generalized Anxiety Disorder-7 questionnaire were used to assess anxiety. Statistical analysis using chi-square. The survey results show that on average Primadonna studio members have quite good sleep quality, as evidenced by PSQI data 16 people (80%) have quite good sleep quality and have minimal anxiety, as evidenced by the results of GAD-7 data as many as 10 people (50%) ) has a minimal anxiety category. Subjects in the moderately good category on average had minimal anxiety and exercised 5 times a week, while subjects in the moderately poor category on average had mild anxiety and exercised 3 times a week It can be concluded that body performance exercise has a good influence on the sleep quality and anxiety of body performance exercise members at Studio Primadonna. The more often and consistently participants do body performance exercises, the anxiety decreases and the quality of sleep improves. Conversely, the less often you exercise, anxiety increases and sleep quality worsens. Future research is expected to be able to link sleep quality, anxiety, and other relevant variables, with varying subjects and views from various perspectives.